2015
DOI: 10.5194/gtes-3-41-2015
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir characterization of the Upper Jurassic geothermal target formations (Molasse Basin, Germany): role of thermofacies as exploration tool

Abstract: Abstract. The Upper Jurassic carbonates of the southern German Molasse Basin are the target of numerous geothermal combined heat and power production projects since the year 2000. A production-orientated reservoir characterization is therefore of high economic interest. Outcrop analogue studies enable reservoir property prediction by determination and correlation of lithofacies-related thermo-and petrophysical parameters. A thermofacies classification of the carbonate formations serves to identify heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
4
31
1
Order By: Relevance
“…The permeability of the Malm carbonate was calculated to be to be 0.69 ×10 −18 m 2 at an applied confining pressure of 25 MPa (an average effective pressure of 12.5 MPa). The measured permeability value is in agreement with those reported by Homuth et al (2015) for Malm carbonate at high effective pressures. At low effective pressures Homuth et al (2015) reported a total shift of about 2-3 order of magnitudes in the permeabilty of the Malm carbonate.…”
Section: Drained and Undrained Conditions In Low Frequency Rangesupporting
confidence: 82%
“…The permeability of the Malm carbonate was calculated to be to be 0.69 ×10 −18 m 2 at an applied confining pressure of 25 MPa (an average effective pressure of 12.5 MPa). The measured permeability value is in agreement with those reported by Homuth et al (2015) for Malm carbonate at high effective pressures. At low effective pressures Homuth et al (2015) reported a total shift of about 2-3 order of magnitudes in the permeabilty of the Malm carbonate.…”
Section: Drained and Undrained Conditions In Low Frequency Rangesupporting
confidence: 82%
“…Majorowicz and Weides, 2014;Weides et al, 2013;Nieuwenhius et al, 2015;Ardakani and Schmitt, 2016). However, an extensive data base on 5 parameters such as porosity, permeability, thermal conductivity, and others, is necessary for a geothermal assessment, especially with complete parameter sets for every single sample (Clauser, 2006;Sass and Götz, 2012;Homuth et al, 2015). This paper reports the results of a pilot study that forms the first phase of a larger project entitled 'MalVonian' (semantically amalgamated from Malm and Devonian), a joint undertaking by researchers from the Technische Universität Darmstadt and the University of Alberta.…”
Section: Introduction 15mentioning
confidence: 99%
“…The Malm-Aquifer in Southern Germany has already been proven to be suitable as a geothermal reservoir (Birner et al, 2012;Homuth et al, 2015;Wolfgramm et al, 2017). However, the overall subsurface data base is relatively scarce because it is mainly based on drill cores from exploration wells, which of there are few in areas without hydrocarbons.…”
Section: Introduction 15mentioning
confidence: 99%
See 2 more Smart Citations